Short- and long-term adverse events in patients on temporary circulatory support before durable ventricular assist device: An IMACS registry analysis - Ton, Van-Khue; Xie, Rongbing; Hernandez-Montfort, Jaime A; Meyns, Bart; Nakatani, Takeshi; Yanase, Masanobu; Shaw, Steve; Pettit, Stephen; Netuka, Ivan; Kirklin, James; Goldstein, Daniel J; Cowger, Jennifer (The Journal of heart and lung transplantation, 2020)
BACKGROUND: Patients with cardiogenic shock (CS) needing temporary circulatory support (TCS) have poor survival rates after implantation of durable ventricular assist device (dVAD). We aimed to characterize post-dVAD adverse event burden and survival rates in patients requiring pre-operative TCS. METHOD: We analyzed 13,511 adults (Interagency Registry for Mechanically Assisted Circulatory Support [INTERMACS] Profiles 1-3) with continuous-flow dVADs in International Society for Heart and Lung Transplantation Registry for Mechanically Assisted Circulatory Support (2013-2017) according to the need for pre-operative TCS (n = 5,632) vs no TCS (n = 7,879). Of these, 726 (5.4%) had biventricular assist devices (BiVAD). Furthermore, we compared prevalent rates (events/100 patient-months) of bleeding, device-related infection, hemorrhagic and ischemic cerebrovascular accidents (hemorrhagic cerebral vascular accident [hCVA], and ischemic cerebral vascular accident [iCVA]) in early (<3 months) and late (≥3 months) post-operative periods. RESULTS: TCS included extracorporeal membrane oxygenation (ECMO) (n = 1,138), intra-aortic balloon pump (IABP) (n = 3,901), and other TCS (n = 593). Within 3 post-operative months, there were more major bleeding and cerebrovascular accidents (CVAs) in patients with pre-operative ECMO (events/100 patient-months rates: bleeding = 19, hCVA = 1.6, iCVA = 2.8) or IABP (bleeding = 17.3, hCVA = 1.5, iCVA = 1.5) vs no TCS (bleeding = 13.2, hCVA = 1.1, iCVA = 1.2, all p < 0.05). After 3 months, adverse events were lower and similar in all groups. Patients with ECMO had the worst short- and long-term survival rates. Patients with BiVAD had the worst survival rate regardless of need for pre-operative TCS. CVA and multiorgan failures were the common causes of death for patients with TCS and patients without TCS. CONCLUSIONS: Patients requiring TCS before dVAD had a sicker phenotype and higher rates of early post-operative adverse events than patients without TCS. ECMO was associated with very high early ischemic stroke, bleeding, and mortality. The extreme CS phenotype needing ECMO warrants a higher-level profile status, such as INTERMACS "0."
Keywords: Heart Transplantation; Heart-Assist Devices; extracorporeal membrane oxygenation; Male; temporary mechanical circulatory support; srdeční selhání; Survival Rate; mortality; ventricular assist device; celosvětové zdraví; Aged; mužské pohlaví; senioři; registrace; transplantace srdce; cardiogenic shock; Global Health; mimotělní membránová oxygenace; lidé; bleeding stroke; ženské pohlaví; intraaortální balónková pumpa; Heart Failure; Humans; Extracorporeal Membrane Oxygenation; podpůrné srdeční systémy; Registries; Intra-Aortic Balloon Pumping; Female; lidé středního věku; míra přežití; adverse events; Middle Aged